Variability of gravitational lens images, caused by variability of gravitational field of lens: binary systems and loops of cosmic strings - I. S. Masniak; B. I. Hnatyk; V. I. Zhdanov (Вісник Астрономічної школи, 2003)
Gravitational lenses with changeable mass distribution cause characteristic changes of image brightness. Detection and analyze of such changes allow us to clarify the nature of the lens. This effect gives a possibility to obtain such dynamical objects as loops of cosmic string. In this article we compare lensing by loops of cosmic string with lensing by binary system. We found parameters and location of these systems, which supply similarity of brightness curves formed by them. We also estimate difference of brightness curves as a function of parameters of these systems. Features of lensing by such loops, which are not peculiar for lensing by binary system, are also discussed.